Changes in short‐chain acyl‐coA dehydrogenase during rat cardiac development and stress. Issue 7 (8th March 2015) - Huang, Jinxian; Xu, Lipeng; Huang, Qiuju; Luo, Jiani; Liu, Peiqing; Chen, Shaorui; Yuan, Xi; Lu, Yao; Wang, Ping; Zhou, Sigui
Abstract This study was designed to investigate the expression of short‐chain acyl‐CoA dehydrogenase (SCAD), a key enzyme of fatty acid β‐oxidation, during rat heart development and the difference of SCAD between pathological and physiological cardiac hypertrophy. The expression of SCAD was lowest in the foetal and neonatal heart, which had time‐dependent increase during normal heart development. In contrast, a significant decrease in SCAD expression was observed in different ages of spontaneously hypertensive rats (SHR). On the other hand, swim‐trained rats developed physiological cardiac hypertrophy, whereas SHR developed pathological cardiac hypertrophy. The two kinds of cardiac hypertrophy exhibited divergent SCAD changes in myocardial fatty acids utilization. In addition, the expression of SCAD was significantly decreased in pathological cardiomyocyte hypertrophy, however, increased in physiological cardiomyocyte hypertrophy. SCAD siRNA treatment triggered the pathological cardiomyocyte hypertrophy, which showed that the down‐regulation of SCAD expression may play an important role in pathological cardiac hypertrophy. The changes in peroxisome proliferator‐activated receptor α (PPARα) was accordant with that of SCAD. Moreover, the specific PPARα ligand fenofibrate treatment increased the expression of SCAD and inhibited pathological cardiac hypertrophy. Therefore, we speculate that the down‐regulated expression of SCAD in pathological cardiac hypertrophy may be responsible for 'the recapitulation of foetal energy metabolism'. The deactivation of PPARα may result in the decrease in SCAD expression in pathological cardiac hypertrophy. Changes in SCAD are different in pathological and physiological cardiac hypertrophy, which may be used as the molecular markers of pathological and physiological cardiac hypertrophy.